Existence and Uniqueness of Almost Periodic Solutions for Neural Networks with Neutral Delays - Min Xu; Zengji Du; Kaige Zhuang (Abstract and Applied Analysis)
A class of neural networks system with neutral delays is investigated. The existence and uniqueness of almost periodic solution for the system are obtained by using fixed point theorem; we extend some results in the references.